Designing a University Batik Motif Based on User Preferences using Conjoint Analysis - Sarika Zuhri; Friesca Erwan; Ilyas Ilyas; Suhendrianto Suhendrianto; Rizki Agam Syahputra; Ratu Cleopatra (Balai Besar Standardisasi dan Pelayanan Jasa Industri Kerajinan dan Batik, 2023)
Batik is one of Indonesia favourite outwears and generally used in formal and semiformal events. This study aims to obtain a university batik motif based on its user preferences, which involving Acehnese motif. This study used stratified random sampling technique to determine 186 batik users who involved as the respondent of this study. The users contributed their perspectives by filling up two steps of questionnaire. The first questionnaire aims to identify user preferences on the design attributes, which consist of logo, the position of logo, Aceh batik motif, fabric basic colour, batik motif colour, and additional batik motif. The second questionnaire aims to obtain the most preference of batik design according to the combination of the attributes. Data obtained from the questionnaires will be analysed using conjoint analysis through SPSS® 22 This study revealed 16 combinations of batik design based on user preferences and the main important attribute in choosing the design was the position of the university logo. Amongst the 16 combinations of batik design, one design shows significant utility value as of 0.543 and determine as the most preferable design chosen by the university batik users.